Effect of explaining radiographic information to the patient before third molar surgery - Christensen, J (The British Institute of Radiology., 2010)
OBJECTIVES: The aim of this study was to compare patient satisfaction with the pre-operative information before and after explaining the radiograph and to compare patient satisfaction with the radiographic information when based on a digital or a conventional image, as well as on extraoral or intraoral images. METHODS: 263 patients (with 301 mandibular third molars) were given pre-operative information by one of two trained scholar students before removal of the third molar. The course of the surgery and possible post-operative complications and risks were explained to the patient. The patients rated their satisfaction with the information on a 100 mm visual analogue scale (VAS). The radiograph was displayed and the radiographic information was explained to the patient, with emphasis on tooth-specific risk factors. The patients again rated their satisfaction on a VAS. RESULTS: There was no significant difference in patient satisfaction score before (mean VAS = 92.5 mm) and after (mean VAS = 91.7 mm) the radiographic information was explained (P = 0.15). No difference in satisfaction was found between patients who were shown either digital or conventional images or between patients who were shown either extraoral or intraoral images (P > 0.5). CONCLUSIONS: No additional patient satisfaction was obtained by showing and explaining the radiograph to the patient before lower third molar surgery. If the dentist still wishes to show the patient the radiograph, the type of image seems not to be important.